Unmet care needs of community-dwelling stroke survivors: a systematic review of quantitative studies - Zhen-Xiang Zhang; Yong-Xia Mei; Shan-Shan Wang; Yao Tong; Bei-lei Lin; Wen-na Wang; Ying-shuang Li; Meng-ya Xu (BMJ Open)
Objectives Understanding the unmet needs of community-dwelling stroke survivors is essential for further intervention. This systematic review was performed to summarise their unmet needs from a quantitative viewpoint.Design Systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources A comprehensive search of six databases was conducted from inception to February 2020: PubMed, EMBASE, CINAHL, PsycINFO, SCOPUS and CBM. The methodological quality of the studies was assessed. Unmet needs were categorised, and a pooled analysis of the main outcomes was conducted.Eligibility criteria for selecting studies We included quantitative studies focused on the unmet needs of stroke survivors who live at homes rather than in any other institutionalised organisation.Results In total, 32 of 2660 studies were included, and 1980 unmet needs were identified. The prevalence of patients with unmet needs ranged from 15.08% to 97.59%, with a median of 67.20%; the median number of unmet needs per patient ranged from 2 to 8 (0–31). The prevalence of unmet needs was high at 6 months post-stroke (62.14%) and 2 years post-stroke (81.37%). After categorisation, the main concerns among these patients were revealed to be information support, physical function and mental health; a few studies reported unmet needs related to leisure exercise, return to work and so on. Additionally, differences in the measurement tools used across studies affect what unmet needs participants report.Conclusions Sufficient, accurate, individualised and dynamic information support is a priority among community-dwelling stroke survivors. Physical function and mental health are also the most significant concerns for re-achieving social participation. It is essential to design and disseminate standard, effective and time-saving tools to assess unmet needs.Trial registration number CRD42018112181.